FIXED FUZZY POINT THEOREMS IN FUZZY METRIC SPACE - Mohinta, S.; Samanta, T. K. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
In this paper, we have established some fixed fuzzy point theorems and common fixed fuzzy point theorems for fuzzy mappings satisfying a contractive type condition other than fuzzy Banach contractive type condition in complete fuzzy metric spaces. 2010 Mathematics Subject Classifications: 47H10, 54E35, 54A40 Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 34-49